2010
DOI: 10.1007/s10930-010-9291-z
|View full text |Cite
|
Sign up to set email alerts
|

Correlation to Protein Conformation of Wide-Angle X-ray Scatter Parameters

Abstract: In the last decade, several studies have reported that Wide-Angle X-ray Scattering (WAXS) from protein in solution contains valuable information about protein secondary and tertiary structures. Nevertheless, the use of such information will remain limited until a clear understanding of the correlation between protein structural elements and WAXS profile regions is established. In this work, large number of possible protein conformations is generated using comparative modeling (LOOPP & PHYRE servers) of nine di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 36 publications
2
23
0
Order By: Relevance
“…The larger domain spacing peak is attributed to either inter-sheet spacing or inter-helix spacing for proteins containing β-sheets or α-helices, respectively. 62 The smaller domain spacing peak arises from inter-strand hydrogen bonding in β-sheet proteins, or backbone hydrogen bonding in α-helices. 62 Given that circular dichroism and the known crystal structure of mCherry suggest a predominantly β-sheet secondary structure, these peaks are inferred to result from inter-sheet spacing and inter-strand hydrogen bonding between β-strands.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The larger domain spacing peak is attributed to either inter-sheet spacing or inter-helix spacing for proteins containing β-sheets or α-helices, respectively. 62 The smaller domain spacing peak arises from inter-strand hydrogen bonding in β-sheet proteins, or backbone hydrogen bonding in α-helices. 62 Given that circular dichroism and the known crystal structure of mCherry suggest a predominantly β-sheet secondary structure, these peaks are inferred to result from inter-sheet spacing and inter-strand hydrogen bonding between β-strands.…”
Section: Resultsmentioning
confidence: 99%
“…62 The smaller domain spacing peak arises from inter-strand hydrogen bonding in β-sheet proteins, or backbone hydrogen bonding in α-helices. 62 Given that circular dichroism and the known crystal structure of mCherry suggest a predominantly β-sheet secondary structure, these peaks are inferred to result from inter-sheet spacing and inter-strand hydrogen bonding between β-strands. Because the q values of these peaks do not change between samples, it is concluded that the inter-sheet and inter-strand spacing is not changed significantly by the processing method used to induce self-assembly.…”
Section: Resultsmentioning
confidence: 99%
“…Two peaks are typically observed in proteins. The first corresponds to a d ‐spacing of approximately 10 Å, and has been attributed to both inter‐helix packing in proteins with predominantly helical structures and to inter‐sheet separation in proteins with a large proportion of β‐sheets . The second is a d ‐spacing of 4–5 Å attributed to repeating distances within each structure, due to hydrogen bonding either along the backbone of α‐helical proteins or between strands in β‐sheets …”
Section: The Crystalline Phasementioning
confidence: 99%
“…The first is attributed to inter‐helix packing in helix rich proteins and inter‐sheet separation in beta sheet rich proteins. The second peak is similarly attributed to either hydrogen bonding along the backbone in helices, or to bonding between strands in β‐sheets . Both were seen in thermoplastics derived from bloodmeal (Figure ).…”
Section: Resultsmentioning
confidence: 94%
“…The second peak is similarly attributed to either hydrogen bonding along the backbone in helices, or to bonding between strands in b-sheets. [17] Both were seen in thermoplastics derived from bloodmeal ( Figure 5). The former peak reduced in size when TEG was included, suggesting some disruption to the packing of ordered secondary structures when TEG was included.…”
Section: Waxsmentioning
confidence: 98%